Inhibition of Return Is Modulated by Negative Stimuli: Evidence from Subliminal Perception - Pan, Fada; Wu, Xiaogang; Zhang, Li; Ou, Yuhong (Frontiers in Psychology, 2017)
Inhibition of return (IOR) is considered as a “blindness mechanism” that emotional stimuli have no impact on it. Most previous studies suggested that IOR was not modulated by emotional cues. However, one key question they ignored was that only supraliminal presentation of emotional stimuli was used in their experiments. The present experiment is aimed at exploring the possible interaction between the IOR effect and subliminal emotional process. We manipulated three different kinds of valence strength of negative stimuli (high negative: HN, moderate negative: MN, low negative: LN) which were presented under the subliminal perception level and an event-related potentials (ERPs) recording was adopted. The results showed that, compared to MN and HN, the IOR effect triggered by peripheral cues was more significant for LN with aspects of behavioral and electrophysiological data (a reduction P1 effect, more negative on cued trials than on uncued trials for both early posterior Nd and Nd components). This indicated that IOR can be modulated by emotionally relevant stimuli. The automatic processing that was triggered by subliminally negative stimuli of peripheral cues had an influence on the shifting of spatial attention that was triggered by IOR. These two mechanisms may occur in the perceptual stage simultaneously.